MULTICULTURAL EDUCATION AS SEEN IN FORREST CARTERS THE EDUCATION OF LITTLE TREE - Ignatius Indra Kristianto (Sanata Dharma University, 2017)
This papers primary purpose is to examine the concept and the impact of multicultural education that is seen in The Education of Little Tree. This paper employs American Studies perspective and Historicism theory in order to obtain the purpose of the study. Using American Studies perspective, this research views Native Americans as indigenous people of America. Using Historicism theory, this research is able to uncover the concept and the impact of multicultural education in the novel by viewing the socio-historical context that is referred by the novel and the socio-historical context when the novel was written and then published. Based on the analysis, it can be concluded that the concept of multicultural education that is seen in the The Education of Little Tree is similar to the concept that is promoted by the experts of multicultural education. The education that is given by the grandparents promotes cultural pride, knowledge of historical information of a culture, and respect towards other cultures. Furthermore, there are several positive impacts of multicultural education that is seen in The Education of Little Tree, they are: first, children possess cultural pride; second, children possess the historical knowledge of their own culture; third, children possess the cultural knowledge of other cultures in their society; and fourth, children respect other cultures in their society.